(untitled) (Pravaha, 2018)
This paper carries the empirical as well as conceptual review regarding the entrepreneurial process and attempts to explore the entrepreneurial process in the tourism and hospitality enterprise creation in semi-urban area of Nepal. Pravaha Vol. 24, No. 1, 2018, Page: 50-57